2020
DOI: 10.1115/1.4045489
|View full text |Cite
|
Sign up to set email alerts
|

A Brain Phantom Study of a Noncontact Single Inductive Coil Device and the Attendant Algorithm for First Stage Diagnosis of Internal Bleeding in the Head

Abstract: Hemorrhagic stroke is one of the leading causes of premature death among economically disadvantaged populations. Treatments of these conditions require an early diagnosis. While computed tomography and magnetic resonance imaging are the medical gold standard for early diagnosis, these imaging modalities are rarely available in low- and middle-income countries. We present an unsophisticated noncontact single coil inductive device and a simple algorithm for detection of changes in fluid/tissue ratio in the head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…6 that all the algorithm values (green markers) which arrived from the one ml group, have values less than 0.5, namely . This is in agreement with our previous article ( Oziel, Korenstein & Rubinsky, 2020 ), in which we showed that this threshold value corresponds to a value that distinguishes small changes of noise and volume of blood from real significant changes of the tissue/fluid volume ratio in the head. A change in the blood/tissue ratio of , which equals to can be used as a measure for the occurrence (a diagnostic index) of a clinical change in the blood/tissue volume ratio.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…6 that all the algorithm values (green markers) which arrived from the one ml group, have values less than 0.5, namely . This is in agreement with our previous article ( Oziel, Korenstein & Rubinsky, 2020 ), in which we showed that this threshold value corresponds to a value that distinguishes small changes of noise and volume of blood from real significant changes of the tissue/fluid volume ratio in the head. A change in the blood/tissue ratio of , which equals to can be used as a measure for the occurrence (a diagnostic index) of a clinical change in the blood/tissue volume ratio.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we developed a very simple and robust algorithm for the single inductive coil configuration ( Oziel, Korenstein & Rubinsky, 2020 ). The algorithm can detect changes in the liquid/gel ratio in the cylindrical configuration of the head ( Oziel et al, 2020 ) with very high accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of bleeding was avoided as much as possible; only minor bleeding was caused during the insertion of the ICP detection probe, and no intervention treatment was carried out after freezing. Some reported studies have shown that intracranial hemorrhage can also cause changes in the ECPS [36][37][38]. It is related to changes in the composition and volume of intracranial contents, which is more complicated than ICP.…”
Section: Discussionmentioning
confidence: 99%
“… Kellner et al (2018) had applied a Volumetric Impedance Phase-shift Spectroscopy (VIPS) device (Cerebrotech Medical Systems, USA) and induced a bioimpedance asymmetry score to assess the severity of stroke. In 2020, Oziel et al used a simple single coil device to detect changes due to fluid volume alteration in the brain, they had proved a sensitivity of 2 ml change in tissue/blood ratio ( Oziel et al, 2020 ; Oziel, Korenstein & Rubinsky, 2020 ). Our research group has been focusing on the diagnosis of brain injuries via Magnetic Induction Phase Shift (MIPS) method.…”
Section: Introductionmentioning
confidence: 99%